Influence of ICT in Road Transportation - S. Suresh; Vasantha S (International Journal of Supply Chain Management, 2018)
Purpose: Information and Communication Technology (ICT) in logistics performance on road transportation is expressed in terms of operation cost and turns rotund time. Though, numerous effects known from the utilization of ICT in the road transportation and importance of vehicle tracking for logistics industry is immeasurable. The most basic use of aGPSdevice is, of course, tracking vehicle locations an extremely useful device to companies that use afleet of vehicles in their line of business. Tracking for logistics industry can alsoprovide information necessary to fleet management for instance if the driver has done his distribution task,the time or estimated time of completion, the place, rapidity, etc. With GPS tracking for logistics industry, youare conscious of the actions of fleet at any given time. Design/methodology/approach: This analysis thus seeks to fill the gap of knowledge by examining the influence of ICT on logistics performance on road transport. Keeping in todays technology requirement, eresources, the leading web-based ERP solution providers in India, offers a powerful and efficient ERP solution for logistic and warehouse management. Practical Implication: This research would be useful to understand the Logistics ERP software symbolizes an advanced manner of organizing, shipping and transport associated processes with comfort and convenience. Findings: This paper scrutinizes the influence of ICT on logistics by conducting a survey of writings on academic logistics magazines, newsletters and articles. It founds an outline for analysing the effect of information technology on road transport in terms of e-commerce, logistics and suggests theoretical mechanisms of impact. Keywords: Information and Communication Technology (ICT), Logistics performance, Enterprise Resource Planning (ERP), Road transport, GPS tracking.